The Effect of Coffee Husk Waste Addition with Alkalisation Treatment on the Mechanical Properties of Polypropylene Composites - Melyna, Ella; Afridana, Atika Pratiwi (Program studi Teknik Kimia UNS, 2023)
ABSTRACT. Indonesia is the fourth largest coffee producing country in the world with 762.38 thousand tonnes production in 2020. The coffee bean waste in the form of coffee skins is around 50-60% of the harvest. Coffee skin waste is a type of natural material that has not been widely used. Processing coffee skin waste as a filler in thermoplastic polymers can be a solution to environmental problems. This study using the polypropylene matrix. This study was conducted to determine the effect of adding coffee husk by alkalizing treatment on polypropylene composites on tensile strength, impact strength and flexural strength. The composition of coffee husk used is 20, 30, 40% wt. The coffee husk was first alkalized with 5%, 8%, and 11% KOH to remove lignin. Composite manufactured using manual forming machines. The results of this study indicate that the addition of coffee husk reduces the value of the tensile strength and flexural strength of the polypropylene composite. The addition of 20% wt coffee husk with 5% KOH alkalisastion on the polypropylene composite gave the highest tensile strength value of 5.65 MPa and the highest flexural strength of 28.72 MPa. Alkalisastion treatment with KOH on coffee husk reduces the value of tensile strength and flexural strength in polypropylene composites. The treatment without 0% KOH alkalisastion on coffee husk gave the highest tensile strength value of 13.30 MPa and alkalizing treatment with 5% KOH on coffee husk gave the highest flexural strength value of 28.72 MPa with the addition of 20% wt coffee husk. Alkalisastion treatment with KOH on coffee husk increased the impact strength value on polypropylene composites. Alkalisastion treatment with 11% KOH on coffee husk gave the highest impact strength value of 4.62 kJ/m2 with the addition of 20% wt coffee husk.Keywords: composite, polypropylene, coffee husk, alkalisation